FUNGSI KELOMPOK KERJA GURU (KKG) BAGI PENGEMBANGAN KEPROFESIONALAN GURU SEKOLAH DASAR - Harun Al Rasyid (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2015)
Abstract: The current study was aimed at describing the functions of the Teacher Work Group (TWG) within the perspective of the continuous professionalism development. The study took place in Kras district Kediri Regency and had 17 elementary school teachers as the research subjects. The data was collected by using interview and inductive analysis. The results of the study suggested that TWG was positively responded by the teachers as the means of sharing knowledge and experiences especially those which were related to the improvement of the teaching and learning quality in the classrooms. TWG was an effective vessel in developing the teachers’ continuous professionalism development. Abstrak: Penelitian ini bertujuan mendeskripsikan fungsi Kelompok Kerja Guru (KKG) dalam perspektif pengembangan profesionalisme berkelanjutan. Lokasi Penelitian di Kecamatan Kras Kabupaten Kediri, dengan subjek 17 guru sekolah dasar. Pengumpulan data dilakukan dengan teknik wawancara dan analisis induktif. Hasil penelitian menunjukkan keberadaan KKG direspon positif oleh guru sebagai sarana berbagi pengetahuan dan pengalaman, khususnya mengenai peningkatan kualitas pembelajaran di kelas. KKG efektif sebagai wadah pengembangan profesionalisme guru secara berkelanjutan.